ANALYSIS OF THE EXCAVATION AND STABILITY METHOD AT THE JOGJA-BAWEN TWIN TOLL ROAD TUNNELS - Adhitya Y.L.A., Boyke
The Twin Toll Road Tunnels of the Jogja-Bawen constructed in Losari village, Grabag, Magelang, Central Java on the Ambarawa-Temanggung section with 550-560 meters length. The construction of the tunnel using NATM methods, horse shoe cross section with dimensions of 19.2 m x 12.8 m and free space dimensions of 15.3 m x 5.2 m. The purpose of this research is to analyze the tunnel excavation methods and the proper support system tunnel as well for the tunnel stability analysis. The research method is analyzed by using the principles of convergence-confinement method to get the initial conditions when excavated the tunnel and tunnel stability analysis refers to JSCE using software Phase 2. The results of the study shows that the deformation at the face is 0.8 m and can be overcome with forepoling wich is a pre-support method to get a minimum displacement value. After forepoling has been installed, the value of roof displacement at the tunnel face decreased by 0.14 cm. The tunnel excavation method acorrding to JSCE (2007) is the side drift excavation method or the three bench and seven step excavation method. Based on the modeling results, after the support is installed are shown safe conditions with a maximum vertical deformation of the roof is 2 cm, the maximum total deformation of a wall is 5 cm, a thickness of the plastic zone on the wall is 2 m and installed rockbolts, and the Strength Factor of rock mass is around 1.4 -2 and SF of support more than 2.